Select physical performance measures and driving outcomes in older adults - Thelma J. Mielenz; Laura L. Durbin; Jodi A. Cisewski; Jack M. Guralnik; Guohua Li (BMC, 2017)
Abstract Background Improving physical functioning may be a future intervention to keep older adults driving safely longer as it can help maintain both physical and cognitive health longer. This systematic review assesses the evidence on the association between three physical functioning measures: the Short Physical Performance Battery, the Timed Up-and-Go test, and the Rapid Pace Walk with driving outcomes in older adults. Methods Older adult studies published between 1994 and 2015 that included the Short Physical Performance Battery, the Timed Up-and-Go test, or the Rapid Pace Walk as a measure of physical functioning and included a driving-related outcome were identified through a comprehensive search and reviewed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results Thirteen studies involving 5,313 older adults met the inclusion criteria. Lower Short Physical Performance Battery scores were associated with reduced driving exposure and increased cessation in all three Short Physical Performance Battery studies. The Timed Up-and-Go test was not associated with the driving outcomes (cessation, ability, crashes, and citations) in either of the two Timed Up-and-Go studies. Poorer Rapid Pace Walk scores were associated with decreased driving ability in two studies and with reduced driving exposure in one study, but not associated with driving ability, crashes, citations, or cessation in the remaining five Rapid Pace Walk studies. Conclusions The Timed Up-and-Go test measure appears not to be a useful measure of physical functioning for the driving outcomes included here. The Rapid Pace Walk may be useful in studies of driving ability and exposure. More driving studies should consider using the Short Physical Performance Battery to determine if it may be useful as a risk factor assessment for identifying individuals at risk of certain driving outcomes.